Comparison of environmental attitudes and experiences of five-year-old children receiving preschool education in the village and city centre - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2016)
The purpose of the study is to compare environmental attitudes and experiences of five-year-old children receiving preschool education in the village and city centre. The first group comprised 54 five-year-old children who received preschool education and attended kindergartens of two primary schools in the Karateke and Kocaba villages of Honaz district in Denizli province, Turkey. The second sample group comprised 50 children receiving education in an independent kindergarten in Merkezefendi district of Denizli province. As data collection tools, Attitude towards Environment Scale and questionnaire of Environmental Experience were used in the study. According to results, environmental attitudes of preschool children living in the village showed a significant difference in favour of children living in the city centre. Examining in terms of gender, it was observed that environmental attitudes of children in both groups did not show a significant difference based on gender.
Keywords: Preschool children; environmental attitude; city-village; urbanisation; STUDENTS